Clinical implications of sperm DNA damage in IVF and ICSI: updated systematic review and meta‐analysis. (1st March 2021) - Ribas‐Maynou, Jordi; Yeste, Marc; Becerra‐Tomás, Nerea; Aston, Kenneth I.; James, Emma R.; Salas‐Huetos, Albert
ABSTRACT: The clinical effect of sperm DNA damage in assisted reproduction has been a controversial topic during recent decades, leading to a variety of clinical practice recommendations. While the latest European Society of Human Reproduction and Embryology (ESHRE) position report concluded that DNA damage negatively affects assisted reproduction outcomes, the Practice Committee of the American Society for Reproductive Medicine (ASRM) does not recommend the routine testing of DNA damage for in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI). Herein, our aim was to perform a systematic review and meta‐analysis of studies investigating whether sperm DNA damage affects clinical outcomes in IVF and ICSI, in order to contribute objectively to a consistent clinical recommendation. A comprehensive systematic search was conducted according to PRISMA guidelines from the earliest available online indexing year until March 2020, using the MEDLINE‐PubMed and EMBASE databases. We included studies analysing IVF and/or ICSI treatments performed in infertile couples in which sperm DNA damage was well defined and assessed. Studies also had to include information about pregnancy, implantation or live birth rates as primary outcomes. The NHLBI‐NIH quality assessment tool was used to assess the quality of each study. Meta‐analyses were conducted using the Mantel–Haenszel method with random‐effects models to evaluate the Risk Ratio (RR) between high‐DNA‐damage and control groups, taking into account the 95% confidence intervals. Heterogeneity among studies was evaluated using the I 2 statistic. We also conducted sensitivity analyses and post‐hoc subgroup analyses according to different DNA fragmentation assessment techniques. We identified 78 articles that met our inclusion and quality criteria and were included in the qualitative analysis, representing a total of 25639 IVF/ICSI cycles. Of these, 32 articles had sufficient data to be included in the meta‐analysis, comprising 12380 IVF/ICSI cycles. Meta‐analysis revealed that, considering IVF and ICSI results together, implantation rate (RR = 0.74; 95% CI = 0.61–0.91; I 2 = 69) and pregnancy rate (RR = 0.83; 0.73–0.94; I 2 = 58) are negatively influenced by sperm DNA damage, although after adjustment for publication bias the relationship for pregnancy rate was no longer significant. The results showed a non‐significant but detrimental tendency (RR = 0.78; 0.58–1.06; I 2 = 72) on live birth rate. Meta‐analysis also showed that IVF outcomes are negatively influenced by sperm DNA damage, with a statistically significant impact on implantation (RR = 0.68; 0.52–0.89; I 2 = 50) and pregnancy rates (RR = 0.72; 0.55–0.95; I 2 = 72), although the latter was no longer significant after correction for publication bias. While it did not quite meet our threshold for significance, a negative trend was also observed for live birth rate (RR = 0.48; 0.22–1.02; I 2 = 79). In the case of ICSI, non‐significant trends were observed for implantation (RR = 0.79; 0.60–1.04; I 2 = 72) or pregnancy rates (RR = 0.89; 0.78–1.02; I 2 = 44), and live birth rate (RR = 0.92; 0.67–1.27; I 2 = 70). The current review provides the largest evidence to date supporting a negative association between sperm DNA damage and conventional IVF treatments, significantly reducing implantation and pregnancy rates. The routine use of sperm DNA testing is therefore justified, since it may help improve the outcomes of IVF treatments and/or allow a given couple to be advised on the most suitable treatment. Further well‐designed controlled studies on a larger number of patients are required to allow us to reach more precise conclusions, especially in the case of ICSI treatments.